Frequency of Ultrasonographically Detectable Fetal Anomalies in Pregnancies Complicated by Polyhydramnios - Sidra Qadir, Maria Younas, Sadiq Jan, Amina Aftab, Muhammad Aiman Waleed Khan, Muhammad Adil Hadeed Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: The diagnosis of polyhydramnios is made prenatally by ultrasound examination using a noninvasive qualitative or quantitative approach. Ultrasound is well suited to assess liquor status and assess amniotic fluid volume. It is non- invasive, easily performed test and had no adverse effects on fetus and mother. 3.5 MHz convex ultrasound transducer (probe) is used to perform sonography, with use of Color Doppler whenever necessary. Objectives: To find out the frequency of ultrasonographically detectable fetal anomalies in pregnancies complicated by polyhydramnios. Study design: Cross sectional study Settings: Radiology Department of PAF Hospital Islamabad. Study duration: 6th October 2020 to 5th April 2021 Materials & Methods: A total of 150 women 20 to 40 years old having polyhydramnios during their second or third trimester of pregnancy were included. Patients with multiple gestation and intrauterine fetal death were excluded. They were scanned in detail with ultrasound machine having a convex 3.5 MHz probe for the severity of Amniotic Fluid Index (AFI) and for congenital fetal anomalies. Patients’ demographics and clinical characteristics were recorded. Results: Age range in this study was from 20 to 40 years with mean age of 28.87±4.16 years. Majority of the patients 92 (61.33%) were between 20 to 30 years of age. Mean gravidity was 3.01 ± 0.99. Mean duration since marriage was 5.50 ± 1.22 years. In this study, frequency of ultrasonographically detectable fetal anomalies in pregnancies complicated by polyhydramnios was found to be 38 (25.33%). Conclusion: This study concluded that frequency of ultrasonographically detectable fetal anomalies in pregnancies complicated by Polyhydramnios is quite high. Keywords: polyhydramnios, fetal anomalies, ultrasonography